Exploring agricultural waste biomass for energy, food and feed production and pollution mitigation: A review. (September 2022) - Babu, Subhash; Singh Rathore, Sanjay; Singh, Raghavendra; Kumar, Sanjeev; Singh, Vinod K.; Yadav, S.K.; Yadav, Vivek; Raj, Rishi; Yadav, Devideen; Shekhawat, Kapila; Ali Wani, Owais
Graphical abstract: Highlights: Efficient agri-waste management can improve food and energy security. Agri-waste can potentially be utilized for industrial use and value addition. Agri-waste would be exploited for second-generation biofuels production. Science led agri- waste management to reduce environmental pollution. Abstract: Globally agricultural production system generates a huge amount of solid waste. Improper agri-waste management causes environmental pollution which resulted in economic losses and human health-related problems. Hence, there is an urgent need to design and develop eco-friendly, cost-effective, and socially acceptable agri-waste management technologies. Agri-waste has high energy conversion efficiency as compared to fossil fuel-based energy generation materials. Agri-waste can potentially be exploited for the production of second-generation biofuels. However, composted agri-waste can be an alternative to energy-intensive chemical fertilizers in organic production systems. Furthermore, value-added agri-waste can be a potential feedstock for livestock and industrial products. But comprehensive information concerning agri-waste management is lacking in the literature. Therefore, the present study reviewed the latest advancements in efficient agri-waste management technologies. This latest review will help the researchers and policy planners to formulate environmentally robust residue management practices for achieving a green economy in the agricultural production sector.